Leadership practices and job involvement: does workplace spirituality moderate the relationship? - Sam Kris Hilton; Albert Puni; Eric Yeboah (Cogent Business & Management, 2024)
As an emerging construct, workplace spirituality has gained credence in organisational management literature due to its effect on work-related behaviours. This paper examines the moderating effect of workplace spirituality on the relationship between transformational, ethical leadership and employee job involvement (EJI) in a developing country. We adopt quantitative approach and cross-sectional survey design to collect data from 416 employees in 10 selected public and private universities in Ghana. We analysed the data using descriptive statistics, correlation and hierarchical regression model. The results indicate that the transformational leadership dimensions and ethical leadership have strong significant positive relationship with EJI. We further establish that workplace spirituality moderates the relationship between ethical leadership and EJI. Regarding transformational leadership, workplace spirituality moderates only the relationship between idealized influence and EJI. The paper provides new findings to bridge the gap in the leadership literature by presenting original evidence that workplace spirituality is an effective moderator in the association between ethical leadership, idealized aspect of transformational leadership and EJI. Additionally, the outcome of this research sparks new discourse, and contributes to organizational practices and policies in Ghana and beyond.
Additional information: Correction available: https://doi.org/10.1080/23311975.2024.2355042
Keywords: 650; Transformational leadership; ethical leadership; workplace spirituality; job involvement